Design and performance of a NaIL detector for neutron/gamma discrimination. (31st August 2021) - Tao, M.; Wang, Z.; Chen, Q.; Li, F.; Qi, J.; Qi, P.; Gao, T.; Zhao, Q.; Zhang, Z.; Zhu, B.; Zhao, C.; Zhou, R.; et al.
Abstract: NaI(Tl+Li) (NaIL) is a promising new inorganic scintillator for thermal neutron detection with the ability for pulse shape discrimination (PSD). In this study, we first built a dual-gamma/neutron sensitive detector based on a NaIL scintillator, a photomultiplier tube and a custom-built circuit. Then, we investigated its temperature response and optimized the PSD parameters, obtaining a figure of merit (FOM) of up to 4.5 at 0–50°C. Also, we examined the effect of the count rate on the detector's neutron and gamma discrimination performance; after optimization, we obtained an FOM of above 3.0 at 5000–40000 counts per second. Lastly, we estimated the neutron detection efficiency of this detector, which is about 13 cps/nv. This detector gave an excellent performance in neutron/gamma discrimination, and can be used widely in the detection of mixed radiation fields.